Molecular Mechanisms of Specific Cellular DNA Damage Response and Repair Induced by the Mixed Radiation Field During Boron Neutron Capture Therapy - Maliszewska-Olejniczak, Kamila; Kaniowski, Damian; Araszkiewicz, Martyna; Tymińska, Katarzyna; Korgul, Agnieszka (Frontiers in Oncology, 2021)
The impact of a mixed neutron-gamma beam on the activation of DNA damage response (DDR) proteins and non-coding RNAs (ncRNAs), is poorly understood. Ionizing radiation is characterized by its biological effectiveness and is related to linear energy transfer (LET). Neutron-gamma mixed beam used in boron neutron capture therapy (BNCT) can induce another type of DNA damage such as clustered DNA or multiple damaged sites, as indicated for high LET particles, such as alpha particles, carbon ions, and protons. We speculate that after exposure to a mixed radiation field, the repair capacity might reduce, leading to unrepaired complex DNA damage for a long period and may promote genome instability and cell death. This review will focus on the poorly studied impact of neutron-gamma mixed beams with an emphasis on DNA damage and molecular mechanisms of repair. In case of BNCT, it is not clear which repair pathway is involved, and recent experimental work will be presented. Further understanding of BNCT-induced DDR mechanisms may lead to improved therapeutic efficiency against different tumors.